Jazz and improvising: experiences, attitudes and beliefs of United Kingdom (UK) secondary school music teachers: listening for gender - Black, Pauline (Frontiers in Education, 2023)
It is well documented that jazz has a male hegemonic narrative. Researchers have also found gender injustices in performance and in education. Recent research has shown that there have been pioneering female jazz musicians around through many eras, however women have traditionally been under-represented in historical jazz narratives and they remain a minority in the field of jazz. This contrasts sharply with the fact that music teaching in schools in the United Kingdom (UK) is a profession occupied predominantly by women. Jazz and improvising occupy a marginal place in the curricula in schools across all four nations in the UK. Studies show that in the secondary school music curriculum there is generally a focus on technical development, musical skill building and reproduction, rather than creative activities such as improvising and composing. There are resultant tensions between the performativity and creativity agendas found in schools and issues of teacher agency, freedom and control are prominent. This mixed methods study of secondary school music teachers (classroom and instrumental) investigates their experiences, attitudes and beliefs in relation to jazz and improvising in their practice. The data show that gender is a significant factor when considering amount and type of activity, as well as confidence and anxiety in jazz and improvising. Barriers exist for women and girls in schools that need to be addressed if changes in gender participation in jazz and improvising are to happen. The study provides implications for future educational practice in order that gender inequities might be addressed.